Effects of moisture stress on growth and yield of selected groundnut (arachis hypogaea l.) Cultivars - Sukanya, M.; Mahendran, S. (University of Jaffna, 2018)
Groundnut is grown in the Batticaloa district of Sri Lanka to a limited extent; the yield is vulnerable to moisture stress especially during the ‘Yala’ season. This experiment was conducted at the Agronomy farm of the Eastern University, Sri Lanka during the ‘Yala’ 2017. Studies were made to determine the effects of moisture stress on growth and yield of selected groundnut cultivars; ‘Lanka jumbo’, ‘Tissa’ and ‘Indi’.Stress was imposed during the flowering stage to find out the most suitable groundnut cultivar which can resist drought and produce substantial yield under water limited situation. Hundred and ninety two groundnut plants of the selected cultivars were raised in polyethylene pots (as one plant per pot). Moisture stress was imposed for a period of ten days during the flowering stage (T2, T4 and T6) and the control plants (T1, T3 and T5) were watered once in two days to maintain at Field Capacity. This experiment was laid out in the Randomized Complete Block Design with six treatments and four replications and the treatments were arranged in 3 × 2 factor factorial manner. There were significant (p<0.05) differences between treatments in the measured parameters. The highest Leaf Area Index (0.78), plant dry weight (1.8g), yield (1.0tha-1) and shelling percentage (59.5%) were obtained in ‘Indi’ groundnut cultivar under stressed condition whereas the lowest Leaf Area Index (0.33), plant dry weight (0.9g), yield (0.33tha 1) and shelling percentage (38.6%) were found in ‘Tissa’ under the same condition. Hence, considering the measured growth attributes, ‘Indi’ groundnut cultivar could withstand drought better than the rest of the cultivars. As such, this cultivar could be suggested for cultivation in the drought prone areas of the Batticaloa district.
Keywords: Groundnut; Leaf area index; Moisture stress; Yield